Simulating social distancing measures in household and close contact transmission of SARS-CoV-2 - Carlos Garcia Filho
We sought to evaluate contact rate reduction goals for household and close contacts and to provide preventive recommendations during the coronavirus pandemic. We applied an agent-based model to simulate the transmission dynamics of SARS-CoV-2 within household or close contacts through a social network of 150 nodes. there is no great difference in total infected people within modifications in number of links per node for networks with average number of links per node greater than three. For six nodes, total infected people are 149.85; for five nodes, 148.97; and for four nodes, 141.57. On the other hand, for three nodes, total infected are 82.39, for two nodes, 13.95; and for one node, 2.96. This model indicates a possible pitfall if social distancing measures are not stepwise suspended and close surveillance of cases are not provided, since the relationship between average links per node and number of infected people seems to be s-shaped, and not linear.